Representação descritiva em assembleias legislativas: gênero e raça como categorias de análise política - Orlando Lyra de Carvalho; Vitor de Angelo (Ciências Sociais Unisinos)
Based on empirical data, this article explores the relationships between the descriptive and substantive representation of women and black people in state assemblies in three regions of Brazil. The proposed model, based on the analysis of roles and electoral socialization mechanisms, compares the descriptive and substantive representation of women (N = 15) with a random sample of male deputies (N = 65), which made it possible to measure possible effects caused by factors such as gender and skin color in the legislative production and in the parliamentary performance of the sampled deputies. Data were collected from the biographical repertoire and legislative production of deputies. Personal interviews were carried out and a questionnaire of 65 items was administered. Correlations between the variables of interest and the profiles of the deputies, their political trajectory, and parliamentary activity were established. A sample of men legislators was compared against a sample of female ones. Compared to the male group, significantly higher rates of female deputies’ specific legislative production were found, although not all members of the descriptive groups behave as ambassadors or ground their parliamentary activities mainly on issues pertaining to democracy of race and gender.